1985
DOI: 10.1094/phyto-75-201
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Watermelon Mosaic Virus II Multiplication inCucumis melo

Abstract: PI 96983 was reported to be conditioned by a dominant gene Rsv virus: Classification based on virulence in resistant soybean cultivars. (5). Resistance to all seven SMV strains transferred from PI Phytopathology 69:467-470. 360.844 to the soybean line OX670 was shown to be conditioned by 3. Cho, E. E., and Goodman, R. M. 1982. Evaluation of resistance in a dominant gene Rsv2 (1). From this study, it was not possible to soybeans to soybean mosaic virus strains. Crop Sci. 22:1133-1136. determine if the genes con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Interchange of melon aphid-resistant and susceptible lines as inoculum plants showed that resistance was to transmission rather than to virus acquisition and concurred with the investigation by Romanow et al (1986) and Lecoq et al (1979Lecoq et al ( , 1980. If resistance to virus multiplication reported by Moyer et al (1985) was present in AR HBJ, it was not reflected in our results and perhaps was masked by the high aphid population. Aphid counts seemed high, but a melon aphid resistant : melon aphid susceptible ratio of 1:3 agreed closely with ratios for previous antibiosis studies (Kishaba et al, 1976).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Interchange of melon aphid-resistant and susceptible lines as inoculum plants showed that resistance was to transmission rather than to virus acquisition and concurred with the investigation by Romanow et al (1986) and Lecoq et al (1979Lecoq et al ( , 1980. If resistance to virus multiplication reported by Moyer et al (1985) was present in AR HBJ, it was not reflected in our results and perhaps was masked by the high aphid population. Aphid counts seemed high, but a melon aphid resistant : melon aphid susceptible ratio of 1:3 agreed closely with ratios for previous antibiosis studies (Kishaba et al, 1976).…”
Section: Discussionsupporting
confidence: 88%
“…Because the same gene governs nonacceptance and resistance to virus transmission, they postulated that the same gene also governs antibiosis. Moyer et al (1985) reported resistance to virus multiplication of watermelon mosaic virus (WMV = WMV 2; Purcifull et al, 1984) in a melon aphid-resistant inbred line from PI 371795. One of our melon aphid-resistant Topmark breeding lines, derived from a cross with a different inbred from PI 371795, lacked this resistance.…”
mentioning
confidence: 99%
“…, 1979; Moyer et a/., 1985). In addition, an increasing number of reports indicate the potential of even slight vector resistance, especially when combined with some forms of virus resistance (Jones, 1979;Lecoq et al, 1979;1980;Moyer et a/., 1985;Gunasinghe et al, 1988); further studies on the use of such plant material in integrated control programmes involving chemical, cultural and biological methods may increase further the effectiveness of virus control (Text- fig. 6; Lecoq & Pitrat, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…A . gossypii-resistant muskmelon also has some resistance to mechanical inoculation with, and multiplication of, watermelon mosaic virus 2 (Moyer, Kennedy & Romanow, 1985) but inhibitors are not involved in this resistance.…”
Section: (D) Specific Interfkretice With Wctor Tratismissioti 41' Rirusmentioning
confidence: 99%
See 1 more Smart Citation